Industrial training report: Hospital Tengku Ampuan Rahimah / Zulaida Manap - Manap, Zulaida (Bachelor of Information Science (Hons.) Records Management, 2015)
All bachelor degree students are required to undergo industrial training for five month as part of their curriculum to complete their 2 year course for the Bachelor of Science (Hons) Record Management. The attachment will be during the 7th semester of their study. During five month period of training, student will be supervised and monitored by two supervisors that are from the faculty and from the organization. Students were required to choose the industrial place for them to do and undertake the training with the organization and from the training, students learned about the skills sets required, demands of the industry, and the work thics. This Industrial Training also gives opportunity to students to put into practice on what they have learned at university besides give benefits to both students and company where the students can get many knowledge while the organization may get the benefits from the quality of support, fresh ideas, and energy that the students bring into the work environment that might be the first experience of working for them.